Indonesia Tingkat Pengetahuan dan Kondisi Lingkungan Terhadap Angka Kejadian Tuberkulosis Paru di RSUD Ratu Zalecha Martapura - Rizka Ayu Wahyuni; Liana Fitriani Hasymi; Reny Marliadi; Muhammad Hadarani (LPPM Universitas Abdurrab, 2025)
Tuberculosis is a disease caused by a bacterial infection. In 2022, Indonesia was recorded as ranked second highest in the world with 969 thousand TB cases and a death rate of 11 deaths/hour from 34 provinces in Indonesia, South Kalimantan Province is one of the provinces whose health centers reported 99% of TB cases in 2022 and hospitals reported 64% of TB cases. Empirically, the risk of TB events is known to be largely driven by the patient's knowledge and age. This study uses a descriptive method. Research sample is an accidental sampling technique in which the number of samples collected during the research period. The results of the research analysis showed that the majority of respondents had a good level of knowledge and had good environmental conditions.